Senyapan dalam Tuturan Berbahasa Indonesia: Studi terhadap Tuturan pada“Debat Pilkada DKI 2017” - Wira Kurniawati (Widyaparwa, 2018)
The purpose of this study is to describe the pause in the production of Indonesian speech in terms of duration, percentage, and reason of pause. This data is released on the pause in the speech delivered by the candidate for governor and vice governor in the event of “2017 Governor Candidate Debate of DKI Jakarta". Data is captured by recording all debate events from the youtube.com. Speech is then transcribed orthographically with the help of Praat version 5, then classified according the purposes. The results show that the existing silence is varied, ranging from very short pause (37 ms) to very long pause (3,633 ms). However, the average pause (499.89 ms) remains in normal pause. The percentage of speaker silence can be said to be quite large because it takes 20.71% or a fifth of the total speech duration. Meanwhile, the reason for pause is divided into two, which is because it is intentional and because it is not intentional. Intentional pause arises from respiration, lingual unit segmentation, grammatical pause, and also expression; unintentional disappearance can occur because of the mental processes experienced by speakers in planning and producing speech, that is because unpreparedness speakers start the utterance, caution choosing words, the mistakes, the pressure, and change the content of the speech.Penelitian ini bertujuan mendeskripsikan senyapan dalamtuturan lisan berbahasa Indonesia dari segi durasi, persentase, serta alasannya. Data diambil dari tuturan calon gubernur dan wakil gubernur dalam acara “Debat Calon Gubernur DKI Jakarta 2017”. Pengumpulan data dilakukan dengan mengunduh keseluruhan tayangan acara dari youtube.com. Tuturan ditranskripsi secara ortografis, lalu diidentifikasi dengan bantuan Praat versi 5, kemudian diklasifikasi berdasar tujuan penelitian. Hasilnya menunjukkan bahwa durasi senyapan sangat variatif, mulai dari senyapan sangat pendek sekali (37 md) hingga sangat panjang (3.633 md). Namun, rata-ratanya (499,89 md)berada dalam senyapan normal. Adapun persentase senyapan cukup besar karena membutuhkan waktu 20,71% atau seperlima lebih durasi bicara total. Alasan penutur senyap ada dua: disengaja dan tidak disengaja. Senyapan yang disengaja terjadi karena pernapasan, segmentasi satuan lingual, jeda gramatikal, serta pemberian ekspresi.Senyapan tidak disengaja terjadi karena proses mental yang dialami penutur dalam merencanakan dan memproduksi tuturannya, yaitu ketidaksiapan memulai tuturan, kehati-hatian memilih kata, adanya kekeliruan, adanya tekanan, dan pengubahan isi tuturan.